Postmortem Handling of Bali Cattle in Slaughterhouse Animal Kolaka District - S. Supriadi (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2020)
This research aims to learn, understand, and know the process of handling Bali cattle at the postmortem stage inanimal slaughtering houseVillage Tahoa District Kolaka. The variables observed in this study consist of the general overview of the slaughterhouses Kolaka, a cutting technique at the animal Slaughterhouse of Tahoa Sub-district Kolaka District, and postmortem examination. Data obtained is then analyzed through a qualitative analysis approach and subsequently concluded. The result of this research is the origin of Bali cattle. The cattle that would cut an animal slaughterhouse came from Timbala, Pomalaa, Ladongi Mowewe, and Rate-rate. The sex of Bali cattle that enter the animal slaughterhouse Kolaka every day on average for the type of cow one tails/day, as well as the female calf Type 1 tail/day. Examination in postmortem in animal Slaughterhouse Tahoa Village District Kolaka Kolaka includes a lymph glandular analysis, meat and pH test of meat, meat color, liver examination, and lung screening. After an excellent cut to be marketed in an indication of 3 things, postmortem health screening is unconditionally permitted, permitted on the condition, or disposed of abnormal and not allowed, delayed, or refused to be exchanged.